Rural Hispanic Health Care Utilization - Marilyn Duran (Rural Nurse Organization; Binghamton University, 2012)
Background and Research Objective: Minority populations living in rural areas are often disadvantaged in their abilities to access healthcare in their community. To further understand the scope of this problem a sample of adult Hispanics residing in three north central Texas rural counties was studied. Sample and Method: A convenience sample of 386 adult Hispanic residents of three rural counties in north central Texas completed surveys about their utilization of health care services in their communities. Results and Conclusions: 74.4 % were uninsured, 72.3% did not have a primary care physician and 63.6% reported they needed access to more health care. Over the past year 23.3 % reported 1-3 visits to the hospital emergency room for health care. Over half (51.3%) reported the need for a translator when going to the doctor. My conclusion is, rural Hispanics are disadvantaged to health care utilization by a lack of health insurance, language barriers and access to a primary care physician.   Key Words: Rural, Access to Health Care, Hispanic